Chromoplast plastoglobules recruit the carotenoid biosynthetic pathway and contribute to carotenoid accumulation during tomato fruit maturation - Zita, Wayne; Bressoud, Ségolène; Glauser, Gaetan; Kessler, Felix; Shanmugabalaji, Venkatasalam (PloS one, 2022)
Tomato ( Solanum lycopersicum ) fruit maturation is associated with a developmental transition from chloroplasts (in mature green fruit) to chromoplasts (in red fruit). The hallmark red color of ripe tomatoes is due to carotenogenesis and accumulation of the red carotenoid lycopene inside chromoplasts. Plastoglobules (PG) are lipid droplets in plastids that are involved in diverse lipid metabolic pathways. In tomato, information on the possible role of PG in carotogenesis and the PG proteome is largely lacking. Here, we outline the role of PG in carotenogenesis giving particular attention to tomato fruit PG proteomes and metabolomes. The proteome analysis revealed the presence of PG-typical FBNs, ABC1K-like kinases, and metabolic enzymes, and those were decreased in the PG of tomato chromoplasts compared to chloroplasts. Notably, the complete β-carotene biosynthesis pathway was recruited to chromoplast PG, and the enzymes PHYTOENE SYNTHASE 1 (PSY-1), PHYTOENE DESATURASE (PDS), ZETA-CAROTENE DESATURASE (ZDS), and CAROTENOID ISOMERASE (CRTISO) were enriched up to twelvefold compared to chloroplast PG. We profiled the carotenoid and prenyl lipid changes in PG during the chloroplast to chromoplast transition and demonstrated large increases of lycopene and β-carotene in chromoplast PG. The PG proteome and metabolome are subject to extensive remodeling resulting in high accumulation of lycopene during the chloroplast-to-chromoplast transition. Overall, the results indicate that PGs contribute to carotenoid accumulation during tomato fruit maturation and suggest that they do so by functioning as a biosynthetic platform for carotenogenesis.